The Relationship Between Hba1c Levels and The Risk of Diabetic Retinopathy in Type 2 Diabetes Mellitus Patients : A Systematic Review - Fahmi Nur Suwandi; Devy Juniarti Iskandar; Charles Sanjaya (The International Journal of Medical Science and Health Research, 2026)
Introduction: Diabetic retinopathy (DR) remains a leading cause of visual impairment worldwide among patients with type 2 diabetes mellitus (T2DM). Glycated hemoglobin (HbA1c) serves as the primary marker of glycemic control, yet the precise nature of its relationship with DR risk requires comprehensive synthesis. This systematic review aimed to evaluate the association between HbA1c levels and DR risk in T2DM patients, examine dose-response relationships, identify effect modifiers, and determine optimal HbA1c thresholds for DR prevention. Methods: A systematic review was conducted following standardized screening criteria. Studies were included if they involved adult T2DM patients, measured quantitative HbA1c levels as an exposure variable, assessed DR as a clearly defined outcome, and examined the relationship between these parameters. Data extraction encompassed study characteristics, HbA1c measurement methods, DR assessment techniques, association measures, and risk factor analyses. Results: Two hundred studies comprising diverse populations across 30 countries were analyzed, with sample sizes ranging from 30 to 175,645 participants. The overwhelming majority demonstrated significant positive associations between elevated HbA1c and increased DR risk. Adjusted odds ratios ranged from 1.60 (95% CI 1.13-2.25) for HbA1c ≥7.5% to 4.23 (95% CI 3.90-4.58) for HbA1c >10%. Dose-response relationships revealed progressive risk increases across HbA1c categories, with optimal screening thresholds identified between 6.6% and 8.15%. HbA1c variability emerged as an independent risk factor beyond mean levels (RR=1.48, 95% CI 1.24-1.78). Significant effect modification was observed with blood pressure, lipid profiles, diabetes duration, nephropathy, and genetic factors. Discussion: The HbA1c-DR relationship demonstrates remarkable consistency across global populations, supporting glycemic control as a cornerstone of DR prevention. The identification of glycemic memory effects and variability as independent risk factors suggests that both achieving target levels and maintaining stable control are crucial. Combined risk factor control produces multiplicative benefits, emphasizing multifactorial management approaches. Conclusion: Elevated HbA1c levels are strongly and consistently associated with increased DR risk in T2DM patients, with evidence supporting target maintenance below 7%. Future research should focus on personalized threshold algorithms incorporating individual risk profiles and investigating interventions targeting HbA1c variability.